Pengaruh Belanja Sosial, Subsidi Pangan dan Belanja Pendidikan Terhadap Tingkat Kemiskinan di DKI Jakarta, DIY dan Bali Tahun 2018-2024 - Risya Aulia Lailli; Saparuddin M; Herlitah Herlitah (Edupreneurship: Jurnal Pendidikan Ekonomi, 2026)
This study aims to analyze the impact of Social Spending, Food Subsidies, and Education Spending on the Poverty Rate in major economic growth centers (DKI Jakarta, DI Yogyakarta, and Bali) during the 2018–2024 period. Despite driving the national economy, these regions experience an urban paradox characterized by distinct inequality and social issues. This research employs a quantitative explanatory approach using panel data regression on 19 observations (unbalanced panel) sourced from Statistics Indonesia (BPS) and the Ministry of Finance. Based on model selection tests, the Common Effect Model (CEM) was chosen as the optimal estimation model, successfully fulfilling all classical assumption tests). The findings reveal that simultaneously, the three independent variables significantly affect the poverty rate, accounting for 68.63% of its variance (R-squared). Partially, Social Spending and Education Spending demonstrate a significant negative effect, indicating that increasing these budgets effectively reduces poverty levels. Conversely, Food Subsidies show no statistically significant partial effect. In conclusion, local government fiscal interventions through social safety nets and human capital development (education) are the most effective instruments for alleviating absolute poverty in these provinces, whereas the implementation of food subsidy policies requires further evaluation regarding targeting accuracy.